Medicinal plants in the treatment of anxiety and depression: A review (Research, Society and Development, 2022)
There is a great diversity of plants in Brazil, and many of them, when studied, have high nutritional content, presence of antioxidant, among other properties, and may have a significant pharmacological potential and consequently generating applications in various areas such as health, cosmetics and cooking. Medicinal plants are used by a large part of the world's population as an alternative medicinal resource for the treatment of various diseases, since in many communities they represent a more accessible resource in various senses in relation to allopathic medicines. The use of medicinal plants for therapeutic purposes is highlighted, in which many biological activities conferred on plants were demonstrated, among them the action on the central nervous system, being used for the treatment and/or prevention of psychosocial disorders such as anxiety and depression. Thus, the present study aims to conduct a literature review on the medicinal plants most used in the treatment of anxiety and depression. It was found that in treatments, medicinal plants and herbal medicines are seen as a viable alternative for the treatment of anxiety and depression, since they have fewer side effects. Thus, the present research reviewed the species: Hypericum perforatum L.; Passiflora incarnata L.; Melissa L. Officinalis; Chamomilla L. recutita; Piper G. methysticum; Erythrina verna; Humulus lupulus L. and Crataegus oxyacantha L. It was possible to present the effectiveness of all the species mentioned, with the descriptions found in studies in the literature.